Ruling Indonesia - Mietzner, Marcus (Michigan State University Press, 2026)
Joko Widodo—popularly called Jokowi—ruled Indonesia for a decade, from 2014 to 2024. The world’s fourth-largest nation and third-largest democracy, Indonesia had embarked on a messy democratic transition in the late 1990s, with the country’s ethnic and religious heterogeneity posing significant challenges to governance. Initially seen as a reformer who might challenge oligarchic structures, Jokowi was slowly but steadily seen as himself being a threat to democracy. By the time Jokowi wrapped up his presidency, he had achieved the highest approval ratings among Indonesia’s post-authoritarian presidents—and became the president with the tightest grip over Indonesia’s political elite. Based on exclusive interviews with Jokowi and many of Indonesia’s top leaders, Ruling Indonesia shows Jokowi as a president obsessively preoccupied with his economic development agenda, subordinating all other aspects of governance to this goal. His focused approach delivered economic successes and unprecedented popularity, but also seriously undermined the health of Indonesia’s democratic institutions. Offering a holistic appraisal of his decade in office, Marcus Mietzner analyzes Jokowi’s domestic record in the context of his attempts to position Indonesia more favorably in the international competition for power and resources. Crucially, his obsession to push Indonesia closer to industrialized status while neglecting democratic development represented the ambitions and trials of many Global South leaders who are trying to juggle economic development, growing Sino-American tensions around the world, and concerns for democratic rights. As such, this book provides valuable insights into how the great power rivalry of the 21st century and the global recession of democracy are playing out in central arenas of the Global South.